A Test Analysis of Fingerprint SMS Gateway System using Black Box Testing Method - Anggi Andriyadi; Dona Yuliawati; Sushanty Shaleh; Nursiyanto Nursiyanto (Proceeding International Conference on Information Technology and Business, 2019)
Fingerprint and SMS Gateway system is one of the alternative technology solutions for Institution, university, school or corporation to state and measure their students and staff discipline. However, most of its technology have note tested yet. This research, will take the sample of one of fingerprint and SMS Gateway Software that previously implemented it at Junior High School 3 Katibung, Lampung. It claim that this application was not only able to provide the information about the student attendance reports through fingerprint but it was also able to provide information to the students’ parents through the SMS Gateway. The aiming of this research is to have analysis testing to determine the validation of data that will inputted through the database with method of Boundary Value Analysis. The result of the analysis is, there are 10% data that failed, therefore there still needs improvements for the system.Keywords: Black Box, Boundary Value Analysis, SMS Gateway, Fingerprint